Assessment of Cases of Stroke in Emergency Department (Academia Journal of Medicine, 2018)
Background: One of the leading causes of death and adult disability among general population is stroke. The efficacy of acute stroke  treatment is very time dependant. This includes both pharmacological and mechanical thrombolysis. Hence; we planned the present study to  assess the cases of stroke which reported to the emergency department of the institution. Subjects and Methods: The present study included  assessment of cases of stroke which reported to the emergency department of the medical institution. A total of 50 cases of stroke were  included in the present study. Complete demographic details of all the patients were obtained. All the results were compiled in Microsoft excel  sheet and were analysed by SPSS software. Results: Dyslipidaemia was found to be present in 80 percent of the patients. Disturbances in speck  and visual disturbances were found to be present in 78 percent and 80 percent of the patients. Motor and sensory symptoms were found to be  present in 72 percent and 64 percent of the patients. Headache and dizziness was present in 84 percent and 78 percent of the patients.  Conclusion: Stoke represent a significant health problem with high mortality and morbidity. It is more common in elderly subjects with  positive history of smoking and dyslipidaemia.
Keywords: Emergency department; Stroke